A comparison of intrathecal dexmedetomidine and clonidine as adjuvants to hyperbaric bupivacaine for gynecological surgery - Anandani, Dipti N.; Shelat, Sejal D.; Vaniya, Jaydeep; Patel, Parth (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Various adjuvants are being used with local anesthetics for prolongation of intraoperative and post-operative analgesia. Dexmedetomidine, a highly selective alpha2 adrenergic agonist, is a new neuraxial adjuvant gaining popularity. The purpose of this study was to compare the onset, duration of sensory and motor block, hemodynamic effects, post-operative analgesia, and adverse effects of dexmedetomidine and clonidine with hyperbaric 0.5% bupivacaine for spinal anesthesia. Methods: 60 patients belonging to ASA Grade 1 and 2 undergoing elective gynecological surgery under spinal anesthesia were studied in this prospective. The patients were allocated in two groups (30 patients each). Group bupivacaine + clonidine (BC) received 17.5 mg of bupivacaine supplemented 45 mcg clonidine and Group bupivacaine + dexmedetomidine (BD) received 17.5 mg bupivacaine supplemented 5 mcg dexmedetomidine. The onset time of sensory and motor level, time to reach peak sensory and motor level, the regression time of sensory and motor level, hemodynamic changes, and side effects were recorded. Results: Patients in Group BD had significantly longer sensory and motor block time than patients in Group BC. The onset time to reach dermatome T4 and modified Bromage3 motor block were not significantly different between two groups. Dexmedetomidine group showed significantly less and delayed requirement of rescue analgesic. Conclusion: Intrathecal dexmedetomidine is associated with prolonged motor and sensory block, hemodynamic stability and reduced demand of rescue analgesic in 24 hrs as compared to clonidine.